IMPLEMENTASI KEWIRAUSAHAAN BERBASIS TEKNOLOGI INFORMASI DAN LITERASI BAHASA INGGRIS DALAM MENINGKATKAN KOMPETENSI LULUSAN SMK NEGERI 1 CIBADAK SUKABUMI - Yoseptry, Ricky; Iriani, Timur; Sutarjo, Tatang; Burhan, Barri Mochamad (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
In the era of disruption, marked by a significant phenomenon of rapid change and characterized by the Industrial Revolution 4.0 and Society 5.0, there has been a profound impact on the workforce, particularly in West Java Province. This aligns with a groundbreaking regulation by the provincial government concerning the establishment of Vocational High Schools (SMK), currently totaling 2,905, and Job Training Institutions (LPK), amounting to 3,170. The primary aim is to create a productive workforce and reduce unemployment rates. This community service activity was conducted at SMKN 1 Cibadak, Sukabumi Regency. The goal of the program was to enhance the knowledge and skills of students at SMKN 1 Cibadak, shaping a resilient and competitive younger generation in the workforce (DUDIKA). The program also sought to develop students' self-potential, creativity, and entrepreneurial character through improved Information Technology competencies and English literacy. The Learning Journey Canvas method was utilized to design and visualize the learning process, while simulation techniques were employed for IT-based English literacy and entrepreneurship training. The expected outcome is that students of SMKN 1 Cibadak, Sukabumi Regency, will acquire proficient entrepreneurial knowledge and skills, enabling them to compete and adapt within DUDIKA. Additionally, they are expected to develop their potential, creativity, and entrepreneurial character while effectively utilizing Information Technology and English proficiency to support their readiness for work, further studies, or entrepreneurship (BMW)